2023
DOI: 10.3390/agronomy13071845
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impacts of Biochar Amendment and Soil Compaction on Unsaturated Hydraulic Properties of Silty Sand

Abstract: The application of biochar as an environmentally friendly additive for agricultural soils has recently gained significant attention. However, the influence of biochar addition on unsaturated hydraulic behavior at high suction ranges (i.e., exceeding 100 kPa) remains largely understudied. This study investigates the impact of biochar addition on the unsaturated hydraulic properties of biochar amended soil (BAS). The effects of biochar content, particle size, and soil compaction on the unsaturated hydraulic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…When a mixture of organic waste is heated to high temperatures between 200 and 900 • C with little to no oxygen or air, the process is known as pyrolysis [10]. Researchers found that adding biochar increased soil permeability by up to 51% when compared to nearby agricultural soils [11]. However, it was discovered that the color, value, and chroma of the charcoal kilns' black soil were reduced by 8, 20, and 20%, respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…When a mixture of organic waste is heated to high temperatures between 200 and 900 • C with little to no oxygen or air, the process is known as pyrolysis [10]. Researchers found that adding biochar increased soil permeability by up to 51% when compared to nearby agricultural soils [11]. However, it was discovered that the color, value, and chroma of the charcoal kilns' black soil were reduced by 8, 20, and 20%, respectively [12].…”
Section: Introductionmentioning
confidence: 99%